Modern approaches to the manufacture of ceramic-matrix composite materials for long-term operation at temperatures above 1000°C. Review of world experience and capabilities of JSC "Kompozit". (November 2019) - Timofeev, P A; Timofeev, I A; Bogachev, E A; Timofeev, A N
Abstract: The article describes modern approaches to the creation of ceramic-matrix composite materials for long-term operation in oxidizing environments. It provides information on advanced technologies for the formation of ceramic matrices and their recipes. The current problems and prospects for the production of such filaments in Russia are discussed.